PENGARUH KONSENTRASI EKSTRAK REBUSAN KULIT KAYU TINGI TERHADAP MUTU KULIT KAKAP PUTIH TERSAMAK - , VANNY RYNY LASMAULY, Dr. Ir. Latif Sahubawa, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of research was to find out the concentration effect of extract stew bark on the quality of tanned skin barramundi. This research used completely random design with treatment concentration bark extract of tingi, they were : 5%(a1), 7.5%(a2), 10%(a3), 12.5% (a4), and 15% (a5 ) with 3 replications. The quality parameters were physical properties [thickness (mm), tensile strength (N/cm2), elongation at break (%), tear strength (N/cm), shrinkage temperature (ÂºC), softness (mm), and chemical properties that is fat content (%)]. The data were analyzed by analysis of variance method and subsequently by Duncan Multiple Range Test (DMRT) on significant of 95% (Î±. 0.05). Based on this research, the thickness of tanned skin of barramundi from each treatment, they were respectively: 0.69